Neurotoxicity and haemostatic disturbances in patients envenomed by the Papuan black snake (Pseudechis papuanus). - Lalloo, D; Trevett, A; Black, J; Mapao, J; Naraqi, S; Owens, D; Hutton, R; Theakston, R; Warrell, D (1994)
Among 335 patients presenting with snakebites in Central Province, Papua New Guinea, nine were proved by enzyme immunoassay to have been bitten by Papuan black snakes (Pseudechis papuanus). Seven showed clinical evidence of envenoming. Early symptoms included vomiting and tender local lymph nodes. Five patients had neurotoxic signs and one required mechanical ventilation. Spontaneous systemic bleeding occurred in two patients. Coagulation studies in four patients showed thrombocytopenia, prolongation of prothrombin time, mild defibrination and depletion of other clotting factors with elevated fibrin(ogen) degradation products and other evidence of fibrinolysis. One patient developed mild renal dysfunction. There was no evidence of intravascular haemolysis or rhabdomyolysis. These clinical observations, which do not distinguish victims of P. papuanus from those of taipans (Oxyuranus scutellatus canni), suggest that the venom contains neurotoxic, haemorrhagic and mild procoagulant activities. Only two other cases of proven envenoming by this species have been reported. There appears to have been a decline in the abundance of this species, and hence its medical importance, over the last 25 years.